REHABILITATION IN SCOLIOSIS - H. Azizova, N. Usmonova, M. Abduhalimova, N. Sobirova (Galaxy International Interdisciplinary Research Journal, 2022)
The information covered in this article is mainly about the rehabilitation of patients with scoliosis and scoliosis with the help of exercises and equipment, as well as with the help of sports equipment and items that can be found at home. and aimed at reducing complications.